2011
DOI: 10.1088/1468-6996/12/2/025003
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the Ca–Mg–Zn system using diffusion couples and key alloys

Abstract: Nine diffusion couples and 32 key samples were prepared to map the phase diagram of the Ca-Mg-Zn system. Phase relations and solubility limits were determined for binary and ternary compounds using scanning electron microscopy, electron probe microanalysis and x-ray diffraction (XRD). The crystal structure of the ternary compounds was studied by XRD and electron backscatter diffraction. Four ternary intermetallic (IM) compounds were identified in this system: Ca 3 Mg x Zn 15−x (4.6 x 12 at 335• C, IM1), Ca 14.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 27 publications
5
24
0
Order By: Relevance
“…Therefore, the purpose of the present research is to investigate the homogeneity range and crystal structure of the Ca 2 Mg 5 Zn 13 ternary compound in the Ca-Mg-Zn system. To be consistent with our previous paper [16], Ca 2 Mg 5 Zn 13 ternary solid solution is addressed as IM3 (intermetallic compound) in this paper.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Therefore, the purpose of the present research is to investigate the homogeneity range and crystal structure of the Ca 2 Mg 5 Zn 13 ternary compound in the Ca-Mg-Zn system. To be consistent with our previous paper [16], Ca 2 Mg 5 Zn 13 ternary solid solution is addressed as IM3 (intermetallic compound) in this paper.…”
Section: Introductionmentioning
confidence: 69%
“…To date, many researchers have studied the Ca 2 Mg 6 Zn 3 compound, but their results are contradictory [9][10][11][12][13][14]. More recently, the solubility range and crystal structure of a Mg-rich solid solution were determined using scanning electron microscopy (SEM), electron probe micro-analysis (EPMA), transmission electron microscopy (TEM) and X-ray diffraction (XRD) by our group [15,16]. In addition, another ternary compound Ca 2 Mg 5 Zn 13 with solubility ranges and its XRD pattern were reported by Clark [10,17], but the crystallographic information was not reported in terms of lattice parameters, space group and structure type.…”
Section: Introductionmentioning
confidence: 99%
“…25) In order to form a specimen consisted of I-phase, Ca 2 Mg 6 Zn 3 and ¡-Mg, alloy composition was determined based on the previously reported MgZnCa ternary isothermal section at 335°C 27) and the calculated MgZnYCa isothermal section at 350°C using Pandat 7 software (data base: Panmg7). As a result, the composition of Mg5 mass%Zn0.8 mass%Y0.3 mass%Ca (Mg1.93 at%Zn0.23 at%Y0.19 at%Ca, hereafter referred to as ZWC) was selected for Ca-containing alloy.…”
Section: Methodsmentioning
confidence: 99%
“…In MgZnCa system, Clark 24,25) reported formation of two ternary compounds: Ca 2 Mg 6 Zn 3 and Ca 2 Mg 5 Zn 13 , and recently Zhang et al 26) reported that the Ca 2 Mg 6 Zn 3 phase has a homogeneity composition range, Ca 3 Mg x Zn 15¹x (4.6¯x¯12). The structure of the Ca 2 Mg 6 Zn 3 phase has been reported to be P6 3 / mmc hexagonal structure 27) or P¹31C trigonal 28) structure. Based on the recent report on the existence of the orientation relationship between Ca 2 Mg 6 Zn 3 and ¡-Mg, 28,29) implying a structural connectivity between two phases, the Ca 2 Mg 6 Zn 3 phase was selected as a secondary phase in addition to the I-phase by addition of Ca in MgZnY alloy.…”
Section: )mentioning
confidence: 99%
“…Several researchers including the research group of the current authors [22,32,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] have been contributing to the development of thermodynamic multicomponent databases of Mg alloys. However, urgency was felt for an open access publication that contains the latest understandings of all the important Mg-based binary systems.…”
Section: Znmentioning
confidence: 99%